The Influence of The Problem-Based Learning (PBL) Model on The Level of Reasoning Ability - Heppy Leunard Lelapary (Journal of Innovation in Educational and Cultural Research, 2022)
The reasoning ability of students at senior high school of 7 Ambon, especially reasoning is still low, so there are still teachers who pay less attention to the reasoning abilities of students. This results in students tending to work on questions fixated on previously given examples without evaluating analysis, synthesis, generalization, connection, and proof. The purpose of this study was to determine the effect of the PBL learning model on the level of reasoning ability of class X students at Senior High School of 7 Ambon on the material of the Indonesian lesson. The approach used in this study is a quantitative approach with the type of research used being quasi-experimental. The sample in this study amounted to 50 people consisting of 25 people in class X1 and 25 people in class X2. Data collection techniques used are observation, tests, questionnaires, and documentation. The data analysis technique used is T-test analysis. Based on the results of the study, it can be concluded that the application of the PBL model affects the level of students' reasoning abilities in the Indonesian lessons subject matter of Indonesian lesson in class X at senior high school of 7 Ambon. It can be seen from the average posttest score of students in the experimental class (X-1) senior high school of 7 Ambon is 72.6, while the average posttest score for students in the control class (X-2) senior high school of 7 Ambon is 60.80. This difference indicates that the level of students' reasoning ability between the experimental class and the control class has a significant difference. This is evidenced by the results of statistical data analysis "T-test" which is obtained by the value of tcount (4,132) ttable (1,711). This proves that the hypothesis is accepted, the application of the Problem Based Learning (PBL) learning model affects the level of students' reasoning abilities in Indonesian subjects in class X SMAN 7 Ambon.